Pengaruh Kombinasi PGPR, Pupuk Kandang Ayam dan NPK Terhadap Pertumbuhan dan Hasil Tanaman Lobak Pada Lahan Sulfat Masam Dengan Sistem Budidaya Jenuh Air - Sarifudin; Purwaningsih; Surachman (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to determine the effect of a combination of PGPR, Chicken Manure and NPK and to find the best dose for the growth and yield of radish plants on acid sulphate land with a water saturated cultivation system. This research will take place from July – September 2023. The research will be carried out at Golden River Camp Jl. Raya Kalimas Hulu, Punggur Kecil, Sungai Kakap District, Kubu Raya Regency, West Kalimantan. The design used was a non-factorial Randomized Block Design (RAK) with 8 treatment levels repeated 4 times. Each experimental unit consists of 4 plant samples. The treatment in question is A = 0 ml/l PGPR + 10 tons/ha chicken manure + 300 kg/ha NPK, B = 15 ml/l PGPR + 10 tons/ha chicken manure + 300 kg/ha NPK, C = 0 ml /l PGPR + 10 tons/ha chicken manure + 600 kg/ha NPK, D = 0 ml/l PGPR + 20 tons/ha chicken manure + 300 kg/ha NPK, E = 15 ml/l PGPR + 10 tons/ha chicken manure + 0 kg/ha NPK, F = 15 ml/l PGPR + 20 tons/ha chicken manure + 0 kg/ha NPK, G = 15 ml/l PGPR + 10 tons/ha chicken manure + 600 kg/ha NPK , and H = 15 ml/l PGPR + 0 ton/ha chicken manure + 600 kg/ha NPK. Observation variables include: number of leaves, leaf area, tuber length, tuber diameter, plant fresh weight, tuber fresh weight, tuber fresh weight, and plant dry weight. The results of the diversity analysis of administering various combination doses of PGPR, Chicken Manure and NPK gave no significant effect on all observed variables. In this study, the combination of PGPR, Chicken Manure and NPK gave equally good results.